Dispersing hydrophilic nanoparticles in nonaqueous solvents with superior long-term stability. Issue 41 (12th May 2017) - Cao, Muhan; Liu, Qipeng; Chen, Min; Yang, Peipei; Xu, Yong; Wu, Haihua; Yu, Jia; He, Le; Zhang, Xiao-Hong; Zhang, Qiao
Abstract : We report a general and robust polymerization–dissolution strategy for phase transfer of hydrophilic nanoparticles into nonaqueous solvents with a 100% transfer efficiency. Abstract : We report a general and robust polymerization–dissolution strategy for phase transfer of hydrophilic nanoparticles into nonaqueous solvents with a 100% transfer efficiency. This process involves the coating of hydrophilic nanoparticles with a layer of linear-chained polystyrene through seeded emulsion polymerization and a subsequent dissolution of polystyrene layer by toluene. Since one end of the linear polystyrene chain is covalently bonded to the particle surface which provides strong steric stabilization, the transferred nanoparticles exhibit superior dispersity and long-term colloidal stability in many nonpolar and polar aprotic solvents. Moreover, the present approach allows for the storage of transferred nanoparticles in a powder form which can be completely re-dispersed in solvents before the usage. Based on this strategy, we demonstrate the phase transfer of Au nanorods and nanospheres, silica, titania and resorcinol-formaldehyde spheres, which just represents a few examples of transferrable hydrophilic nanoparticles with different morphologies, sizes, compositions, functions and surface properties. This general and robust phase transfer protocol will greatly facilitate the applications of hydrophilic nanoparticle in organic catalysis, optoelectronics, energy storage and conversion, and organic light emitting diodes.